THE ANTI - VIOLENCE VERSES IN THE TEN COMMANDMENTS OF GOD FROM THE PERSPECTIVE OF JUDAISM, CHRISTIANITY AND ISLAM - Satria Tenun Syahputra (el-'Umdah, 2021)
Abstract: Comparative study of religion or widely known as interreligous studies understood by a great deal of people as a study focused on finding out only the differences between religions and faith. Even though the study can be benefited to find out the similarities rather then differences, so that can be a starting point to campaign the non – violance’s action interreligion. This research tend to find out the similarities in the Jews, Christian and Islamic teachings, by analizing the ten commandments that has the same content in the three religions, so that can be summarized about the verses contain the non – violance narrative in the ten commandments. This article is a library research with a comparative method by the content analysis qualitatif approachment to reveal the messages conveyed by the media and to analize the media as a content transmitter. The result of the reasearch is the ten commandmends verses contained the non – violance narrative that if it is implemented by every religion’s people from the Jews, Christian and Islam, it could prevent the violance among the people, like the violence in family, violence in neighbors, community and interreligious violence. This kind of research must be developed, rather then to argue about the differences, it will be good to find out the similarities to create the peaceful interreligious life. Abstrak: Studi komparati antar agama atau yang lebih dikenal luas dengan interreligious studies banyak dipahami oleh sebagian kalangan dengan kajian yang terfokus untuk mencari perbedaan antar agama dan keyakinan saja. Padahal studi komparatif juga bisa dimanfaatkan untuk mencari titik persamaan antar agama, sehingga dengan ditemukannya keselarasan (similarities) di dalam ajaran agama masing – masing, hal itu bisa menjadi titik tolak untuk menggaungkan sikap anti- kekerasan antar agama. Penelitian ini bertujuan untuk mencari titik keselarasan dalam ajaran agama Yahudi, Kristen dan Islam, yaitunya dengan menganalisa sepuluh perintah Tuhan (ten commandments) yang memiliki redaksi sama dalam ketiga ajaran, untuk kemudian disimpulkan mengenai ayat – ayat yang mengandung narasi anti – kekerasan dalam sepuluh perintah Tuhan tersebut. Penelitian ini merupakan kajian pustaka (library research) dengan metode komparatif menggunakan pendekatan analisis isi kualitatif untuk mengungkap pesan – pesan yang disampaikan oleh suatu media serta menganalisa media tersebut sebagai penyampai pesan, dari hasil penelitian ditemukan bahwa ayat – ayat sepuluh perintah Tuhan mengandung narasi anti kekerasan yang apabila diaplikasikan oleh setiap agama, baik Yahudi, Kristen dan Islam, maka akan mencegah kekerasan antar sesama dan antar agama seperti kekerasan dalam keluarga, kekerasan dalam bertetangga dan kekerasan dalam masyarakat. Hal seperti ini perlu dikembangkan, dari pada membahas tentang perbedaan, lebih baik mencari persamaan agar tercipta kehidupan antar agama yang damai dan sejahtera